E-Learning By Using Google Classroom At English Education Department Of STAI Hubbulwathan Duri - Khoir, Abdul; Deswarni, Dini (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
Today, there are many online learning platforms. New technology is developed to facilitate the learning process. One example of online learning the platform is Google Classroom. The purpose of this research is to identify students responses to E-Learning by using Google Classroom in the English Education Department of STAI Hubbulwathan Duri.This research used survey research. Survey research provides a quantitative or numeric description of trends, attitudes, or opinions of a population by studying a sample of that population. Research subject population as many as 33 students of the English Education Department Semester 3, 5, and 7. The research method is quantitative and adapted research Shaharanee et.al (2016) questionnaire as an instrument to collect data. The questionnaire contains 15 items. The Google classroom application iseffective to recommend in learning because it provides various benefits for both students and lecturers the results show that in Using Google Classroom students feel satisfied and useful Google Classroom as online learning tools